Studies on the Causes, Impacts and Mitigation Strategies of Landslide in Chittagong city, Bangladesh - Mia, MT; Sultana, N; Paul, A (Journal of Environmental Science and Natural Resources, 2016)
Landslide is becoming a regular hazard in the urbanized hilly areas in Chittagong, Bangladesh. Generally, the hills consist of unconsolidated sedimentary rocks such as sandstone, siltstone, shale and conglomerate. Applying questionnaire survey with 120 respondents, and collection of secondary information, the study was carried out in two landslide prone sites located in Batali hill and Motijhrna area of Chittagong city for assessing the socio-economic condition of the people, causes of landslide, impacts of landslide on local people and mitigation strategies of landslide. People living in the study area were characterized by dominance of middle age group of population (52%), illiterate (49%), day laborer (27%), migrated from the other places (93%), low income (57%) and having poor housing infrastructure. The present study indicates that landslide affect the poor people living on the slope of hilly areas. The main reasons identified for landslide were hill cutting (36%), weak soil structure (23%) and devegetation (16%). The major impacts of landslide on the local communities, as reported by the respondents were loss of natural scenic beauty (77%), economic loss (77%), destruction of lives (57%) and environmental problems (47%). According to the respondents, the main mitigation strategies were stopping of hill cutting (75%), resettlement of the affected people in other places (57%), planting the affected area (55%) and development of robust policy (42%). J. Environ. Sci. & Natural Resources, 8(2): 1-5 2015